Peningkatan Karakter Disiplin melalui Apel Pagi Bagi Siswa SD Muhammadiyah 22 Surakarta - Choirun Nisa; Soleh Sundava; Ismi Azizah (Departement of Mathematics Education, 2023)
The purpose of this research is to tell that how the formation of character in discipline and behavior to students by running routine programming in order to get results when creating good behavioral character and applied to students at SD Muhammadiyah 22 Surakrta. The method that researchers use is a qualitative descriptive research method, the data that researchers take and researchers use is qualitative data. Researchers get information from the acquisition of data, either directly to the object of purpose or indirectly. As well as the interview stage with the teachers of SD Muhammadiyah 22 Surakarta. The subjects in this study were students and teachers and employees at SD Muhammadiyah 22 Surakarta. From the data information obtained after conducting the research, the researcher found that the results of the morning apples that are routinely carried out can be used as a place and a good bridge in order to create and give birth to a disciplined, responsible character, etc. and can make students have a sense of courtesy and can respect teachers and friends.